PERILAKU PEMILIH PADA PEMILIHAN UMUM LEGISLATIF 2019 DI GAMPONG TAMPANG KABUPATEN ACEH SELATAN - Chadijah, Devi Intan; Arza, Asyatul; Srilesari, Yeni; Sariyanti, Lilis (Jurnal Society : Pengamat Perubahan Sosial, 2024)
This research was conducted to find out how voters behaved in the 2019 legislative elections in Gampong Tampang. The aim of this research is to determine the factors that influence the political behavior of the people of Tampang Gampong in determining their choices in the 2019 legislative elections. This research uses a qualitative descriptive method with a purposive sampling technique for determining informants and a purposive sampling technique for determining informants and data collection techniques in the form of interview. and documentation. The research results show that voting behavior is influenced by three factors. First, social factors consisting of indicators of age, education, employment and economic status and religion. Second, psychological factors, which consist of 2 indicators, namely political and emotional identities built by legislative candidates and their teams. Third, economic factors. The indicators that are influenced by economic factors are related to welfare. If voters from the lower class will choose candidates who offer programs related to opening up job opportunities, voters from upper class economic status will focus more on candidates who guarantee political stability which is closely related to decision making that will have an impact on the voter's own income.